The The Impact of Workload and Job Insecurity toward Employee Work Stress due to Covid-19 Pandemic (Case Study at LA Hotel Seminyak) - Adi Pratama, I Wayan; Santi Diwyarthi, Ni Desak Made; Citrawati, Luh Putu; Darmiati, Made (Jayapangus Press, 2024)
This study aimed to investigate how job insecurity and workload, both individually and in combination, affected employee work stress at LA Hotel Seminyak during the Covid-19 pandemic. The data for this research were collected through various methods, including observation, interviews, documentation, and questionnaires. A total of 36 respondents participated in the study, and a saturated sampling technique was used. The data analysis involved classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and the determination of the coefficient of determination. The findings of this study revealed that job insecurity, when considered individually, had a positive and statistically significant impact on employee work stress. Similarly, workload, when examined in isolation, also had a positive and significant effect on employee work stress. When both job insecurity and workload were considered together, they collectively had a significant influence on employee work stress. The coefficient of determination test indicated that job insecurity and workload together accounted for 66.0% of the variance in work stress, while the remaining 34.0% was attributed to other variables not addressed in this study.